U-PB AND 207PB-206PB AGES OF ZIRCONS FROM BASALTIC EUCRITES: IMPLICATIONS FOR EARLY BASALTIC VOLCANISM ON THE EUCRITE PARENT BODY - Misawa K.; Yamaguchi A.; Kaiden H. (My University, 2005)
We have undertaken petrologic and SHRIMP U-Th-Pb isotopic studies on zircons from basaltic eucrites (Yamato [Y]-75011, Y-792510, Asuka [A]-881388, A-881467 and Padvarninkai) with different thermal and shock histories. Eucritic zircons are associated with ilmenite in most cases and have subhedral shapes in unmetamorphosed and metamorphosed eucrites. Some zircons in highly metamorphosed eucrites with granulitic texture occur alone in pyroxene, and typically have rounded to subrounded shapes due to recrystallization. Superchondritic Zr/Hf ratios of eucritic zircons indicate that they crystallized from incompatible element-rich melts after crystallization of ilmenite. Concentrations of uranium and thorium in zircons in the unmetamorphosed eucrite Y-75011 are higher than those in metamorphosed eucrites.